Research on Optimization Design and Processing Technology of Engine Intake System Based on NX and Fluent - Zhang, Jun; Gao, Ruqian; Wu, Yangfang (Manufacturing Technology Journal, 2025)
To design an engine intake system that complies with FSC racing regulations while achieving enhanced operational stability, this study conducts a comprehensive review of domestic and international research advancements in racing engine intake systems. Through computational fluid dynamics simulations performed in Workbench Fluent, critical structural parameters of the restrictor valve were optimized, resulting in a 12.06% improvement in outlet mass flow rate compared to the baseline design. A three-dimensional parametric model of the racing intake system was developed using Siemens NX platform. Taking the intake plenum chamber as a representative component, this research systematically analyzes the CNC machining process for the mold of the pressure stabilization chamber. The investigation encompasses toolpath generation, cutting simulation verification, and ultimately implements the optimized NC program on machining centers for physical manufacturing. The fabricated mold exhibits high dimensional accuracy and superior surface finish, providing both theoretical guidance and practical manufacturing references for intake system development. This integrated approach combining numerical optimization with advanced manufacturing techniques demonstrates significant potential for performance enhancement in motorsport engineering applications.
Keywords: Intake system; Fluent; NX; Processing technology